2009
DOI: 10.1007/s11255-009-9534-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of apocynin and losartan treatment on renal oxidative stress in a rat model of calcium oxalate nephrolithiasis

Abstract: These results suggest that renal Ang II and its stimulation of NADPH oxidase may partially account for the development of OS in kidney in this rat model of CaOx nephrolithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…Nox have since been identified as the major source of ROS that sustains the up-regulation of MCP-1 and osteopontin in renal tubular epithelial cells in response to hyperoxaluria [137,138]. Administration of AT 1 R blockers such as candesartan or losartan in stone-forming rat models reduced Nox activity and crystal deposits in the renal interstitium, corroborating that not only do Noxes become activated in hyperoxaluria conditions, but that they also play a key role in stone formation [139,140]. As such, it is probable that oxidative stress through Nox-derived ROS is a major contributor of renal cell injury, epithelial cell adhesion to crystallites and stone formation.…”
Section: Kidney Stones (Nephrolithiasis)mentioning
confidence: 87%
See 1 more Smart Citation
“…Nox have since been identified as the major source of ROS that sustains the up-regulation of MCP-1 and osteopontin in renal tubular epithelial cells in response to hyperoxaluria [137,138]. Administration of AT 1 R blockers such as candesartan or losartan in stone-forming rat models reduced Nox activity and crystal deposits in the renal interstitium, corroborating that not only do Noxes become activated in hyperoxaluria conditions, but that they also play a key role in stone formation [139,140]. As such, it is probable that oxidative stress through Nox-derived ROS is a major contributor of renal cell injury, epithelial cell adhesion to crystallites and stone formation.…”
Section: Kidney Stones (Nephrolithiasis)mentioning
confidence: 87%
“…Stone formation occurs in a precise manner to allow crystallization, nucleation, growth and aggregation of urinary crystals and renal cell injury is a critical event in allowing crystal-cell interaction. Direct inhibition of Nox activity with apocynin in Sprague-Dawley rats with ethelene glycol-or hydroxyl-L-proline (HLP)-induced hyperoxaluria reduced CaOx crystal deposits as well as the expression of renal injury and inflammatory markers [139,141]. Administration of AT 1 R blockers such as candesartan or losartan in stone-forming rat models reduced Nox activity and crystal deposits in the renal interstitium, corroborating that not only do Noxes become activated in hyperoxaluria conditions, but that they also play a key role in stone formation [139,140].…”
Section: Kidney Stones (Nephrolithiasis)mentioning
confidence: 99%
“…Our previous studies demonstrated that hyperoxaluria and crystal deposition induced the production of ROS and renal epithelial cells injury in a rat model of calcium oxalate nephrolithiasis [27, 28]. Mitochondria are generally the most common intracellular sources of ROS, and cellular injury is usually accompanied by the production of ROS [29].…”
Section: Discussionmentioning
confidence: 99%
“…The source of ROS in tissue injury is largely dependent on the types of enzymes activated. The NOX family has been identified as a major source of superoxide and hydrogen peroxide in the kidney during health and disease [13,22,23,24,25]. NOX consists of at least one membrane-bound NOX/p22-phox complex and cytosolic subunits p67-phox, p47-phox, p40-phox as well as the small GTPase rac1 or rac2.…”
Section: Discussionmentioning
confidence: 99%